The research on the evolution of long-term intercompany supply chain collaboration and its influence factors based on the life cycle theory - QINYU, WANG (2015)
In today’s increasingly fierce competitive marketing environment, supply chain collaboration is employed by more and more companies as core competitiveness to obtain competitive advantage. Supply chain collaboration is considered to be dynamic. The dissertation researches on the evolution of long-term intercompany supply chain collaboration and its influence factors by taking long-term intercompany collaborative relationships as the unit of analysis. The life cycle theory is introduced to study supply chain collaboration. The dissertation mainly explores the evolution of supply chain collaboration from the life cycle perspective and investigates the way in which influence factors affect the maintenance of supply chain collaboration. Two real cases of supply chain collaboration illustrate the analysis and findings of the dissertation. The life cycle model of long-term intercompany supply chain collaboration is built. The study points out that long-term intercompany supply chain collaboration would experience four stages that are introduction, adjustment, development and maturity. Characteristics of each stage are affected by strategies and management that companies applied. Influence factors would affect the level of collaboration and the re-willingness of collaboration of collaborators, and then impact the maintenance of supply chain collaboration. The dissertation also puts forward the viewpoint that the relative importance of influence factors is different at various stages.